Validation of the Indonesian Version of the Epistemological Belief Questionnaire - Laras Firdaus; Masiah Masiah; Ibrohim Ibrohim; Sri Rahayu Lestari (Bioscientist : Jurnal Ilmiah Biologi, 2021)
The lack of studies on epistemological beliefs in Indonesia is the background for this research, with the availability of the Indonesian version of the questionnaire of epistemological beliefs, it is hoped that it can help practitioners who want to study epistemological beliefs. The purpose of this study was to validate the Indonesian version of the epistemological belief questionnaire which was adopted from the epistemological belief questionnaire developed by Conley et al. (2004). A total of 124 prospective teachers as voluntary respondents in this study, consisting of 20 biology prospective teachers form The Mandalika University of Education, 49 prospective teachers for science education from IAIN Salatiga, 25 biology prospective teachers from The Madiun University of Education, and 30 biology prospective teachers from The Muhammadiyah University of Malang. The data obtained were then analyzed using the exploratory factor analysis (EFA) technique using SPSS version 22 for windows, while confirmatory factor analysis (CFA) was performed using SPSS Amos version 24 for windows. Based on the results of the EFA analysis, the KMO value = 0.755, it was stated that the data met the criteria for factor analysis. Furthermore, from the results of the CFA, of the 17 items from the EFA analysis, 15 items were obtained that support a fit model, with a P-value = 0.081, CFI = 0.960, TLI = 0.950, NFI = 0.819, and RMSEA = 0.050, and it was concluded that 15 items are declared valid and reliable.